2020
DOI: 10.3390/ijms21030839
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Transporter-3 Knockout Mice Demonstrate Age-Dependent Alterations in the Metalloproteome

Abstract: Metals are critical cellular elements that are involved in a variety of cellular processes, with recent literature demonstrating that zinc, and the synaptic zinc transporter (ZnT3), are specifically involved in learning and memory and may also be key players in age-related neurodegenerative disorders such as Alzheimer’s disease. Whilst the cellular content and location of metals is critical, recent data has demonstrated that the metalation state of proteins is a determinant of protein function and potential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…All three metals were increased in the disease model mice compared to wild-type controls, and their speciation was also altered, with a trend towards less protein-bound metal. A study by the same team of labs using the same approach found that mice that lack the zinc transporter ZnT-3 had altered speciation for not only Zn, but also Fe and Cu [138].…”
Section: Animal Cells and Tissuesmentioning
confidence: 99%
“…All three metals were increased in the disease model mice compared to wild-type controls, and their speciation was also altered, with a trend towards less protein-bound metal. A study by the same team of labs using the same approach found that mice that lack the zinc transporter ZnT-3 had altered speciation for not only Zn, but also Fe and Cu [138].…”
Section: Animal Cells and Tissuesmentioning
confidence: 99%
“…ZnT3 knockout mice are deficient in total zinc concentrations at both three and six months. ZnT3 is known to be heavily involved in learning and memory and also to play a major role in aging-related neurodegenerative diseases [ 69 ]. Our laboratory has demonstrated that synaptic zinc is an important factor for modulating hippocampal neurogenesis, and we used ZnT3 knockout mice to address this question.…”
Section: Friendmentioning
confidence: 99%
“…Interestingly, our results demonstrate lower Zn levels in the retina, hippocampus, and cortex of APP/PS1 compared with WT mice. A likely explanation for our finding is based on the fact that previous studies have shown that Zinc Transporter 3 (ZnT3) proteins are essential for loading Zn into synaptic vessels [ 89 , 90 , 91 ]. These proteins are abundantly available during the early stages of AD and its only with ageing that ZnT3 levels are depleted resulting in higher levels of free Zn.…”
Section: Discussionmentioning
confidence: 99%